The CMS Barrel Calorimeter Processor demonstrator (BCPv1) board evaluation. (1st August 2022) - Loukas, N.; Goadhouse, S.; Anderson, T.; Belloni, A.; Gorski, T.; Grassi, T.; Hakala, J.; Hirosky, B.; Jessop, C.; Lutton, L.; Madorsky, A.; Mariano, J.; et al.
Abstract: For the CERN LHC phase 2, the barrel region of the CMS electromagnetic (ECAL EB) and hadronic calorimeters (HCAL HB) require new back-end electronics for their readout. To this purpose, a first version of the ATCA-based blade, the Barrel Calorimeter Processor (BCPv1), has been developed. The performance of the optical links as well as clock distribution are also presented here. The BCPv1 has been tested together with front-end and trigger boards, as well as with the new DAQ and TCDS Hub (DTH) [1], to demonstrate that the BCPv1 meets the required specifications.